Liquidity, Solvency, and Profitability as Determinants of Firm Value: Empirical Evidence from the Food and Beverage Subsector on the Indonesia Stock Exchange - Andi Muara Arumbarkah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the effects of liquidity, solvency, and profitability on firm value in food and beverage companies listed on the Indonesia Stock Exchange during 2019–2022. Research Method: An explanatory quantitative design was employed using secondary data obtained from audited financial statements and annual reports. The purposive sample comprised 17 companies and 68 firm-year observations. The data were analyzed using pooled multiple linear regression and supporting regression diagnostics. Results and Discussion: Liquidity, proxied by the Current Ratio, has a positive and significant effect on PBV. Solvency, proxied by the Debt-to-Equity Ratio, has a negative and significant effect, while profitability, proxied by Return on Assets, has a positive and significant effect. The three variables are jointly significant, with R² = .511 and adjusted R² = .488. Implications: Managers should maintain adequate but productive liquidity, align leverage with cash-flow capacity, and improve the productivity of assets in generating earnings. Investors should read CR, DER, and ROA jointly rather than treating each ratio in isolation when evaluating consumer-sector firms. Originality: It integrates signaling theory with the trade-off perspective to explain why liquidity and profitability convey positive valuation signals, whereas leverage may signal heightened financing risk.